Music therapy for depression: A narrative review - Xiaoman Wang; Wei Huang; Shuibin Liu; Chunhua He; Heng Wu; Lianglun Cheng; Songqing Deng (Brain-X)
Abstract As living standards improve, mental and physical health have been gaining increasing attention. Presently, depression is one of the most severe mental health issues. Depression affects the quality of life of affected individuals because it lasts for a very long time and is generally difficult to cure. Currently, pharmacotherapy and psychotherapy are the two main approaches for treating depression. However, some principles and characteristics of pharmacotherapy remain unclear, and its side effects are significant and noticeable. In addition, ordinary psychotherapy requires the assistance of a qualified psychotherapist, which is usually hard to find and expensive. Both methods are burdensome to the patients, making it difficult for them to benefit. As an easy‐to‐obtain therapy, music therapy has been recommended by physicians as an auxiliary therapy for various diseases to regulate patients' emotions and help the primary treatment methods to obtain better therapeutic effects. This review investigates and summarizes recent articles on the pathogenesis of depression and the effects of music therapy on depression. Its results show that music therapy is effective and available. However, a systematic treatment plan has not yet been formulated due to the lack of samples and short follow‐up times. Future studies should include more samples and follow‐up patients after the treatment period to address the continuous effect and principle of music therapy.